Built-in flexibility of taxation and stability when tax liabilities respond with a time lag .1. Comment - Bradley, James F. (Economic & Social Studies, 1976)
In the October 1975 issue of The Economic and Social Review, D. J . Smyth examined the built-in stability of a system when tax liabilities are a lagged function of income. Taking an unlagged and a distributed lag consumption function he showed that the existence of a lagged tax function could be destabilising, causing damped, regular or explosive oscillations.
Keywords: Economics; Tax; Ireland